The Relevance of Thematic Hadith Studies on Al-Rahbāniyyah to The Contemporary Issue of Singlehood - Umam, Khaerul; Fudhaili, Ahmad (Jurnal Penelitian Ilmu Ushuluddin, 2025)
The phenomenon of singlehood has sparked debate among Muslims regarding its compatibility with religious teachings. This study uses a descriptive qualitative method by exploring thematic hadith studies based on the term al-rahbāniyyah (singlehood). Meanwhile, the approach used in this study is a theological approach (maqashid al-sunnah) elaborated with a sociological approach. The results show that even though al-rahbāniyyah is historically associated with monastic practices that are criticized in the Qur’an (57:27), thematic hadith studies offer more nuanced insights into balancing spiritual devotion and social responsibility. By analyzing hadith thematically through the keyword al-rahbāniyyah, this study successfully demonstrates how Islamic tradition navigates individual autonomy, marital obligations, and communal ethics, while also providing a critical lens for addressing the issue of celibacy in the modern era. The results of this study conclude that the thematic insights of al-rahbāniyyah encourage inclusive dialogue about celibacy, promoting flexibility in Islamic law while maintaining core ethical principles.